PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN TOKO FANNY TEXTILE JAKARTA - Joni Efendi; Nur Azizah (JURNAL MITRA MANAJEMEN, 2019)
From the data processing perfomed using SPSS 20 for window, obtained multiple correlation coefficient (R) = 0.975, which means that there is a strong relationship or positive, and in the can (R2) at = 97.5% and the remaining 4.3%. To obtain the value of the multiple regression Y = 3.101 + 0.394 X1+ 0.340 X2+0.422X3 and for t test with a confidence level α = 5% obtained t value of 1.683 that there is a significant positive effect between the variable X1 to Y, and that there are significant positive significantly between variables X2 to Y, and there is a significant positive influence between the variables X3 to Y then Ho is rejected and Ha accepted, which means there is the influence of Product Quality, Price, and Location on Customer Satisfaction. As well as for the F–test with a confidence level α = 5% obtained Fvalue of 0.000 which is smaller than the value of the trust which means that the variables X1, X2, X3 are jointly significant effect – variable equal to Y. therefore it can be concluded that the regression model used in this study is correct and feasible.